Acute myocardial infarction therapy: in vitro and in vivo evaluation of atrial natriuretic peptide and triphenylphosphonium dual ligands modified, baicalin-loaded nanoparticulate system - Jie Wang; Shouwen Zhang; Lizhe Di (Taylor & Francis Group, 2021)
Background Myocardial infarction (MI) is one of the most common ischemic heart diseases. It is very essential to explore new types of cardioprotective drugs delivery systems in this area. Objective The aim of the present study was to investigate the protective effect of baicalin (BA) and puerarin (PU) against acute MI rat models. BA and PU co-loaded nanoparticulate system were developed to improve bioavailability of the drugs, to prolong retention time in vivo and to enhance the protective effect. Methods In the present study, ANP and TPP contained ligands were synthesized. ANP/TPP-BN-LPNs were prepared and its physico-chemical properties were evaluated. The MI therapy efficiency of ANP/TPP-BN-LPNs was assessed in rats after intravenous injection. Single ligand contained LPNs, no ligand contained LPNs, and BN solution formulations were also prepared and used for the comparison. Results ANP/TPP-BN-LPNs were uniform and spheroidal particles. The size of ANP/TPP-BN-LPNs was 98.5 ± 2.9 nm, with a zeta potential of -19.5 ± 1.9 mV. The dual ligands modified LPNs exhibited significantly improved therapeutic efficiency compared with the single ligand modified LPNs and other systems. In vivo infarct therapy studies in rats proved that ANP/TPP-BN-LPNs were a promising system for efficient delivery of cardiovascular drugs for the treatment of cardiovascular diseases. Conclusions ANP/TPP-BN-LPNs could be used as a long-circulating and heart-targeting drug delivery system.